Religious Authority Poetry Adnan AL-Sayegh,s (Journal of the College of Education for Women, 2019)
After this stage in the Bible is problematic and the profane in the poetry of the AL-Sayeghs,and found that the poems path heading towards obey religious authority because of their willsand powers, and the insurgency in other areas, as it did not employ shady methods and punsand intriguing, and I find the reason for this is due to the fear poet focused toward theinfluence of political Sergeant, more than effusion direction ascendancy religious sergeant,was a AL-Sayeghs stop at this border; but went to the formulations problematic diversity inthe cognitive system, he tries it all to critique, as submitted by the history of the conflictsproduced generations of oppression and conflict and tension (what my fault I was born Sunnior Shiite), and if the debt problem is to impose on human wills before his creation, to producehim in the future of the conflict, which is not responsible for it.